A Systematic Literature Review on Knowledge Representation Approaches for Systems-of-Systems - Abdalla, Gabriel; Damasceno, Carlos Diego N.; Guessi, Milena; Oquendo, Flavio; Nakagawa, Elisa Yumi (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2015)
Systems-of-Systems are a class of systems composed of diverse, independent constituent systems. Together, these constituents can accomplish missions that otherwise could not be performed by any of them separately. In another perspective, knowledge representation approaches can assist in the establishment of a common understanding in this field by formalizing and standardizing the main terms and concepts adopted. In spite of the relevance of SoS, a consolidated terminology which could support the community working with such systems is still missing. Furthermore, the multiplicity of stakeholders, technologies, and expertise involved in an SoS makes the need of a common understanding even more imperative. In this study, we report on the main findings of a systematic literature review covering knowledge representation approaches in the SoS field. With this study, we are able to present a comprehensive panorama of the knowledge representation approaches that are currently adopted. Even though a consolidated terminology is not available yet, such panorama can be helpful for devising a common, comprehensive terminology for the SoS field. Therefore, we conclude this paper with directions for future work.